Islamic Spiritual E-Leadership Integration Model for Education Quality Improvement in the Digital Era - Sutrisno, Sutrisno (Didaktika Religia, 2024)
This research explores the integration of Islamic spiritual leadership and e-leadership in improving the quality of education in madrasahs. Islamic spiritual leadership emphasizes ethical, moral and spiritual values as the basis for decision-making and daily actions. In the context of madrasahs, this leadership not only aims to achieve academic excellence but also create an environment that supports learners' spiritual development. This research supports the theory that effective leaders in Islamic education inspire and motivate through exemplary worship and good morals, as exemplified by the Prophet Muhammad. E-leadership utilizes information and communication technology to facilitate the learning process and school management. Using PLS-SEM analysis, this study found that madrasah principals who combine spiritual values with technological capabilities can create a school culture that is more adaptive and responsive to change. The analysis showed that Islamic spiritual leadership significantly affects the quality of education, with the mediating influence of E-leadership. The integration of these two approaches enables madrasahs to remain relevant in the digital age, increase accessibility and flexibility in the learning process, and ensure education rooted in strong Islamic values. This research provides a foundation for the development of effective leadership models to improve the quality of education in madrasahs in the digital era.